2003
DOI: 10.1159/000069019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects on Selected Oral Bacteria of Antibacterial Agents Incorporated in a Glass Ionomer Cement

Abstract: The objectives of the study were to investigate the antimicrobial efficacy, over time, of combining antibacterial agents with a glass ionomer cement (GIC). This was assessed using an agar diffusion test. Chlorhexidine hydrochloride, cetylpyridinium chloride, cetrimide and benzalkonium chloride were added to Fuji IX GIC at 0, 1, 2 and 4% w/w. Antibacterial-GIC specimens were placed onto agar plates inoculated with one of six bacterial species (Streptococcus, Lactobacillus and Actinomyces, two each) and the area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
120
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(133 citation statements)
references
References 2 publications
7
120
1
5
Order By: Relevance
“…The largest number of studies analyse the antimicrobial effect of the chlorhexidine compound in the form of diacetate, gluconate, digluconat, hydrochloride or dihydrochloride, incorporated in conventional and modifi ed glass-ionomer cements, most often in the powder of the glass-ionomer cements (14,16,17,18,29,31). The antimicrobial effect against the cariogenic microorganisms Streptococcus mutans, Lactobacillus casei and Actinomyces viscosus is most often analysed (16,18,29,31).…”
Section: Discussionmentioning
confidence: 99%
“…The largest number of studies analyse the antimicrobial effect of the chlorhexidine compound in the form of diacetate, gluconate, digluconat, hydrochloride or dihydrochloride, incorporated in conventional and modifi ed glass-ionomer cements, most often in the powder of the glass-ionomer cements (14,16,17,18,29,31). The antimicrobial effect against the cariogenic microorganisms Streptococcus mutans, Lactobacillus casei and Actinomyces viscosus is most often analysed (16,18,29,31).…”
Section: Discussionmentioning
confidence: 99%
“…The generalised and inherent formation of pores within the GIC reduces its strength to flexion and cohesion 20,11 . These pores are regions of high concentration of stress, which increased the likelihood of fracture of the material 22 .…”
Section: Discussionmentioning
confidence: 99%
“…This association is aimed at reducing severity and frequency of secondary caries by decreasing failures and unsuccessful use of these restorative materials 6,7,12,25 . Based on the observation of the presence of viable bacteria in the remaining dentin after removal of the infected layer and proper sealing of the cavity researchers observed that under in vitro conditions the addition of CHX to the GIC showed favorable antibacterial effect against microorganisms such as Streptococcus mutans, Lactobacillus spp., Candida albicans and Actinomyces naeslundii, acts on the biofilm act on the biofilm, which begins to show less pathogenic composition compared to acidogenic biofilm with a predominance of S. mutans, which would be formed without the presence of the antibacterial agent 3,9,[11][12][13][14]23,25 Türkün et al 3 demonstrated that GIC and CHX at a concentration of 0.5% have a long-term antibacterial effect without compromising the physical properties of the restorative material. However, concentrations at 1.25 and 2% weaken the material by compromising its physical properties, such as resistance to erosion, compression, diametrical traction, flexion, setting time, and surface hardness 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When shear bond test was used, other studies also showed that the application of CHX did not have a negative effect on the bond strength of adhesive systems [25,26]. On the other hand, one study even reported increased shear bond strength when CHX was used [27].…”
Section: Discussionmentioning
confidence: 99%